Belief in Pigs' Capacity to Suffer: An Assessment of Pig Farmers, Veterinarians, Students, and Citizens. (2nd January 2020) - Peden, Rachel S. E.; Camerlink, Irene; Boyle, Laura A.; Loughnan, Steve; Akaichi, Faical; Turner, Simon P.
ABSTRACT: Intensive animal production practices lead to animal suffering worldwide. This study examined whether farmers cope with the negative impact of farming practices on their animals by ascribing them less capacity to suffer compared with other species. Most people like eating meat but find animal suffering emotionally disturbing. Human omnivores employ a variety of strategies to navigate this "meat paradox, " and one of these is to reduce their perception of animals' capacity to suffer. Psychological defenses associated with meat-eating have been widely researched, but this study provides the first investigation into how these are employed amongst those involved in meat production and focusses on intensive pig producers as an example. Seventy-six pig farmers reported their belief in pigs' capacity to experience pain, hunger, fear, and boredom in a paper-based survey employing visual analogue scales. Their responses were compared with their perceptions of livestock that they did not farm (cows) and two companion animal species (dogs and cats). These results were compared with people who had similar experience of working with pigs (15 specialized pig veterinarians) and those who had no experience of pigs (23 agricultural students, 22 animal science students, and 58 citizens unrelated to agriculture). The results of the 194 responses provide evidence to suggest that the pig farmers did not ascribe their animals a diminished capacity to suffer. Rather, pig farmers expressed an enhanced belief in pigs' capacity to experience hunger. All comparison groups expressed widespread belief in each species' capacity to suffer. Nevertheless, dogs were the species judged to be most capable of suffering, and animal science students gave the highest suffering scores overall. Farmers are directly responsible for the welfare of their animals, and further investigation into the psychological and behavioral strategies of farmers may provide insight into non-financial reasons behind the generally slow progress in improving animal welfare.